Tibial plateau fracture and RNA sequencing with osteogenesis imperfecta: a case report - Chen, Yixiao; Li, Guoqing; Wei, Liangchen; Weng, Jian; Liu, Su; Gu, Mingxi; Liu, Pei; Zhu, Yuanchao; Xiong, Ao; Zeng, Hui; Yu, Fei (Frontiers in Endocrinology, 2023)
Osteogenesis imperfecta (OI), is a hereditary skeletal dysplasia with an incidence of about 1:15000 to 20000. OI is usually caused by the mutation of COL1A1 and COL1A2, which would encode the α-chain of type I collagen. OI is clinically characterized decreased bone mass, increased risk of bone fragility, blue sclerae, and dentinogenesis. Case Presentation: A 29-year-old male patient was diagnosed with right tibial plateau fracture caused by slight violence. Physical examinations: height in 140 cm, weight in 70 kg, with the body mass index (BMI) being 35.71 kg/m2, blue sclera and barrel chest were observed. X-ray examination showed left convex deformity of the thoracic vertebrae with reduced thoracic volume. Laboratory examinations revealed of both decrease of vitamin D and blood calcium. Bone mineral density (BMD) was lower than the normal range. After the preoperative preparation were completed, the open reduction and internal fixation of the right tibial plateau fracture were performed. Meanwhile, whole blood samples of this OI patient and the normal control were collected for RNA transcriptome sequencing. The RNA sequence analysis revealed that there were 513 differentially expressed genes (DEGs) between this OI patient and the normal control. KEGG enriched signaling pathways were significantly enriched in extracellular matrix (ECM)-receptor interactions. Conclusion: In this case, DEGs between this OI patient and the normal control were identified by RNA transcriptome sequencing. Moreover, the possible pathogenesis of OI was also explored, which may provide new evidence for the treatment of OI.